DECIPHERING THE INTERPLAY BETWEEN BLOCKCHAIN TECHNOLOGY AND SUPPLY CHAIN MANAGEMENT: AN IN-DEPTH ANALYSIS OFLITERATURE AND EMERGING TRENDS - Loso Judijanto; Muh. Rezky Naim; Mohammad Ahmad Bani Amer (Adisam Publisher, 2024)
Blockchain technology has arisen as a promising answer for upgrading straightforwardness, recognizability, and productivity in overseeing supply chains. This examination paper digs into the complex connection between blockchain innovation and production network the board, amalgamating existing writing and pinpointing arising patterns. By fastidiously inspecting scholastic examination and industry reports, this study enlightens the bunch advantages of incorporating blockchain into supply chains, including uplifted straightforwardness, lessened extortion, and reinforced cooperation among partners. Furthermore, it examines the obstacles frustrating blockchain execution, going from adaptability issues to difficulties in interoperability and administrative consistence. Through an inside and out investigation of contextual investigations and experimental proof, this paper reveals insight into commonsense uses of blockchain across different areas of production network the executives. Additionally, it distinguishes incipient patterns and future examination roads, for example, synergizing blockchain with other state of the art innovations like the Web of Things (IoT) and computerized reasoning (man-made intelligence) to fashion more wise and versatile production network environments. By unwinding the groundbreaking capability of blockchain in store network the executives, this study improves academic comprehension as well as offers noteworthy experiences for both scholarly world and industry professionals.